4-nor-β-Patchoulene sesquiterpenoids from the essential oil of Pogostemon cablin. (June 2015) - Liu, Jian-lin; Li, Xiao-hong; Peng, Cheng; Lin, Da-sheng; Wang, Ya-nan; Yang, Yu-ting; Zhou, Qin-mei; Xiong, Liang
Graphical abstract: Highlights: Four unusual nor -β-patchoulene sesquiterpenoids were obtained from Pogostemon cablin . 4- nor -β-Patchoulenes were first reported from natural sources. The isolates were assayed for cytotoxic activity on human cancer cells. Abstract: Four nor -β-patchoulene sesquiterpenoids including three new compounds (1 –3 ) and a new natural product (4 ) were isolated from the essential oil of the leaves and stems of Pogostemon cablin . Their structures were elucidated by detailed spectroscopic analysis, using 1D- and 2D-NMR techniques. This is the first report of 4- nor -β-patchoulenes from plants. All isolates were evaluated for the cytotoxic activities on human cancer cells in vitro . Compound 3 showed weak cytotoxic activities against NCI-H1975 and HePG-2 with IC50 values of 49.9 μg/mL and 56.0 μg/mL, respectively.